A New Impedance Measurement System for PZT-Based Structural Health Monitoring - Baptista, Fabricio Guimaraes [UNESP]; Vieira Filho, Jozué [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Recent research has shown that electromechanical (E/M) impedance-based techniques are an efficient strategy for damage sensing in the context of structural health monitoring (SHM). The basic principle is to excite the lead zirconate titanate (PZT) sensors attached to the structure and to measure the corresponding electrical impedance. A variation in the electrical impedance indicates a variation in the mechanical impedance and, consequently, structural damage. To measure the electrical impedance, most universities and research centers use expensive, bulky, heavy, and high-powered impedance analyzers, which limit new developments and practical applications. To overcome these issues, this paper presents an efficient and inexpensive methodology for electrical impedance measurement. To verify the efficiency and accuracy of the new methodology, practical tests were carried out, and the results were compared with those obtained using a conventional impedance analyzer.
Keywords: Impedance analyzer; smart structures; structural health monitoring (SHM); virtual instrumentation